The influence of CI electrode array design on the preservation of residual hearing - Fries, L.; Everad, F.; Beck, R. L.; Aschendorff, A.; Arndt, S.; Ketterer, M. C. (Frontiers in Neurology, 2025)
ObjectivesTo individualize cochlear implant (CI) surgery regarding cochlear morphology, different electrode arrays have been developed. The study aims to investigate the influence of the electrode array design on the preservation of residual hearing, considering long-term results.MethodsWe performed a retrospective analysis of 923 patients implanted with straight or perimodiolar electrode arrays from Cochlear™ and MED-EL between 2003 and 2021. The standard pure tone average (PTA4) and low-frequency PTA (PTAlow) were measured before and after surgery, with a follow-up period of 3.2 years up to 15.7 years.ResultsIn patients with measurable preoperative PTA4 (data of four frequencies), the slim straight electrode array (SSA) was chosen significantly more often preoperatively within the Cochlear™ portfolio (CA vs. SSA p = 0.007) and the Flex24 within the MED-EL portfolio (FlexSoft vs. Flex24p = 0.0085). The electrode array design significantly influences the preservation of residual hearing, both in low-frequency PTA and standard PTA. The electrode arrays with the most favorable performance in terms of long-term residual hearing preservation appear to be the slim straight electrode array (SSA) from Cochlear™ and the Flex24 from MED-EL, with no statistical differences from other electrodes.ConclusionPreoperative residual hearing influences the choice of electrode array within the manufacturer’s portfolio, with short electrode arrays showing superior results in the preservation of residual hearing. Over time, straight and short electrode arrays are associated with improved preservation of residual hearing. Therefore, for patients with existing relevant residual hearing, it is advisable to choose short and atraumatic lateral wall electrode arrays.